Anticipating Ocean Deoxygenation in the Maritime Continent of Southeast Asia - Ita Wulandari; A'an J. Wahyudi; Karlina Triana (ASEAN Journal on Science and Technology for Development, 2021)
Oxygen plays an essential role in the biogeochemical process and ocean productivity, especially during the recent trend of climate change. Development of the oxygen loss condition, deoxygenation, receives less attention than ocean acidification and warming. Therefore, understanding deoxygenation is indispensable. The maritime continent waters of Southeast Asia (SEA) are well-known for marine biodiversity and unique geological features. The area is inevitably impacted by climate change and will suffer more due to less oxygen in seawater. Based on previous research, Bengal Bay has been affected by oxygen depletion and climate change, in which hypoxic rate conditions continuously increase. In the other SEA area, seasonal hypoxia occurs in coastal areas as an impact of eutrophication. This occurs in Sangga Besar River Estuary, Bolinao and Anda coastal waters, Manila Bay, Jakarta Bay, and Cambodian waters. Deoxygenation anticipation is an essential step as a response to the development of oxygen loss areas, and monitoring is proposed as a preliminary step before the oxygen loss worsens. This review focuses on observing oxygen depletion changes and hypoxia in the maritime continent area, including its potency, effect, and recommendations on how to monitor deoxygenation.